The Effect Hellp Syndrome on Neonatal Asphyxia in Margono Soekarjo Hospital Purwokerto - Sumarni; Fitria Prabandari; Dyah Puji Astuti (Proceeding of International Conference on Science, Health, And Technology, 2021)
Introduction: hellp syndrome is a dangerous condition that occurs in pregnant women with preeclampsia. Hellp syndrome occurs in 10-20% of cases of pre-eclampsia. The characteristics of the HELLP syndrome include; thrombocytopenia, hemolysis (microangiopathic hemolysis anemia) and abnormal liver enzymes. The main causes of perinatal death associated with the incidence of HELLP syndrome include; prematurity, intrauterine growth restriction (IUGR), asphyxia, placental insufficiency, and placental abruption. The objective was to determine the effect of Hellp syndrome on neonatal asphyxia in pregnant women with preeclampsia. The method used was descriptive analytic with approach cross sectional. The number of samples used was 42 people with purposive sample technique Data analysis used thetest chi square. Result shows that there is a relationship between Hellp syndrome and neonatal asphyxia in pregnant women with preeclampsia with a value of p = 0.036, OR: 5.464, which means that babies born to pregnant women with Hellp syndrome are at 5,464 times more likely to experience asphyxia than pregnant women with preeclampsia without hellp syndrome. Conclusion: There is a relationship between Hellp's syndrome with neonatal asphyxia in pregnant women with preeclampsia